Cutting-Edge Agricultural Technology for Farmer Self-Reliance: Support and Implementation of Efficient Spraying Equipment - Kusnanto, Kusnanto; Sumarni, Margaretha Lidya; Usman, Usman (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
Agriculture plays a crucial role in Indonesia's economy but faces various challenges such as climate change and low productivity. To address these issues, technological innovation is essential. Efficient modern agricultural sprayers are one key innovation that helps farmers apply pesticides and fertilizers more effectively. This study focuses on the support and implementation of efficient sprayers in Bana Village, Teriak District, Bengkayang Regency. Through lectures, discussions, demonstrations, and simulations, farmers are encouraged to understand and adopt this technology. The results show an increase in farmers' knowledge and skills in using the sprayers, as well as improved crop productivity and reduced chemical usage. The participatory approach in this study ensures practical and sustainable solutions, enhancing farmer self-reliance. It is hoped that the implementation of this technology will improve farmer welfare and support agricultural sustainability in Indonesia.